Relationship between lending interest rate, inflation rate and capital formation in Kenya - Titus Mosoti Ogero (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The study seeks to understand the relationship between lending interest rate, inflation rate and capital formation in Kenya. Time series from World Bank for the 1988 to 2018 is employed. Development of literature is guided by expectation theory, classical theory of interest rate and the institutionalist theory of capital formation. The study finds capital formation, lending interest rate ad inflation rate time series data to be stationary at the 5% level of significance. This leads to the checking of the lag order used and estimating of VAR model. The results indicate that, current year’s; capital formation, inflation rate and lending interest rate are insignificant in determining next year’s level of capital formation. First lag of inflation rate is found positively significant in influencing lending interest rates as well as the first lag of lending interest rate is found significant on influencing itself. Capital formation first lag is found to be negatively significant in determining inflation rate. Lastly, inflation rate first lag is found to be positive